Přeprava automobilů z České republiky do Kazachstánu - Shiryayeva, Madina; Madina Shiryayeva (České vysoké učení technické v Praze, 2021)
Cílem bakalářské práce „Přeprava automobilů z České republiky do Kazachstánu“ je charakteristika přepravního procesu automobilů z České republiky ze společnosti Škoda Auto a.s. do Kazachstánu, analýza stávající přepravní cesty automobilových dílů a návrh alternativního trasování.

The aim of the bachelor thesis "Transport of cars from the Czech Republic to Kazakhstan" is to characterize the transport process of cars from the Czech Republic from the company Škoda Auto a.s. to Kazakhstan, an analysis of the existing transport route of car parts. The bachelor's thesis also proposes an alternative transport route.
Transportation of cars from the Czech Republic to Kazakhstan
Keywords: Kazachstán; automobilový průmysl; Škoda Auto; mezinárodní přeprava; export; import; železniční doprava; Kazakhstan; automotive industry; Škoda Auto; international transport; export; import; railway transport